Answer:
6.2y - 3.7
Step-by-step explanation:
−y+5.3+7.2y−9
Subtract 9 from 5.3 to get −3.7.
−y−3.7+7.2y
Combine −y and 7.2y to get 6.2y.
6.2y−3.7
Answer:
(4x - 3)(3x² + 1)
Step-by-step explanation:
Given
12x³ - 9x² + 4x - 3 ( factor the first/second and third/fourth terms )
= 3x²(4x - 3) + 1(4x - 3) ← factor out (4x - 3) from each term
= (4x - 3)(3x² + 1) ← in factored form
Answer:
According to the sample data, we can claim that the current satisfaction rate is different from last year's.
Step-by-step explanation:
The explanation is in the picture.
Answer:
D
Step-by-step explanation:
to find a term in the sequence multiply the previous term by r , then
a₄ = - 8 , so
a₅ = - 8 × 0.5 = - 4
a₆ = - 4 × 0.5 = - 2
If Lalo has 5 apples and tito took 3 the answer is 2